The place of the law in the religion of ancient Israel - Weinfeld, Moshe (Supplements to Vetus Testamentum ;, 2004)
Over a hundred years ago, Wellhausen attempted to prove that the Priestly legal sections of the Pentateuch reflect postexilic Judaism and must be considered a deviation from the prophetic religion preceding it. In this study, Weinfeld points out the fallacies in Wellhausen's thesis, making a case for the antiquity of the Priestly Code. Particular a.